Inter State Variations in Education Enrolment Patterns in India (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Education plays an important role in building self-confidence among women it also enables to change she/her status in the society. Education enables and builds confidence to take decisions in a better way. A quality education is the foundation of sustainable development. Education for sustainable development ensuring equal access for all women and men to affordable and quality technical, vocational and tertiary education, including university; and eliminating gender disparities in education and ensure equal access to all levels of education and vocational training for the vulnerable, including persons with disabilities, indigenous peoples and children in vulnerable situations. The present paper mainly aims to study on the regional inequalities in the enrolment on education at macro level; to have a descriptive analysis on the State wise and Level wise enrolment Patterns, Disparity in Education Enrolment; to analyse the extent of inequalities in education in India; and to offer possible strategies for strengthening the education and bridging the interstate variations in India. The study is a descriptive study based on secondary data mainly gathered from Various Issues of Educational Statistics – At a Glance, published by Government of India, Ministry of Human Resource Development, New Delhi and The Unified District Information System for Education Plus (UDISE Plus) published by the Department of School Education & Literacy, Ministry of Education, Govt of India. Based on the UDISE Plus report it is observed that the GPI for primary education in India stands at 1.03, indicating a slight favorability towards girls. Several states and union territories show encouraging numbers, such as Andaman and Nicobar Islands (1.05), Arunachal Pradesh (1.01), Bihar (1.03), and Delhi (1.07). These regions demonstrate a relatively higher enrollment ratio for girls at the primary level, contributing to gender parity in early education. At the Upper Primary level, the Gender Parity Index for India is 1, indicating equal participation of girls and boys. Achieving universal school education by 2030 demands a multi-faceted approach, to achieve the goal; India must address systemic challenges through targeted policy interventions to bridge gaps in access, quality, and equity, ensuring every child receives a meaningful education. India’s policy ecosystem for strengthening the education sector as a whole with the introduction of the NEP, updated guidelines, regulations for academic collaboration and mutual recognition of qualifications, building more world class infrastructures, providing welfare facilities and permissions for foreign branch campuses. Further, India's education sectors require unwavering focus to unlock the nation's true potential through integrated, accountable, and adaptive policy frameworks to build a future ready workforce.